ANALISIS ALIH FUNGSI LAHAN PERTANIAN BERDAMPAK TERHADAP TINGKAT KETAHANAN PANGAN PETANI KENTANG DESA BULAN JULU, DI KEC. BARUS JAHE - Posman HP Marpaung; Fandri Siburian; Cornelius Tarigan; Enda Warista Putra Jaya Sitepu (JURNAL AGROTEKNOSAINS, 2023)
Development and development of the quality of farming communities in carrying out farming is one aspect that supports the creation of increased agricultural production and productivity, so that profits can be increased. Agricultural development, especially horticultural crops that have been implemented, has made a positive contribution to economic development. The clearer and more obvious that the economic system is, the more it is influenced by the agricultural sector. This sector has an impact on the sustainability of the income of farmers in an area.Cultivation of vegetable crops in Indonesia is generally carried out with monoculture and polyculture cropping patterns. Monoculture is a cultivation system in an area of land planted with only one type of plant. Meanwhile, polyculture is a system of plant cultivation in the same area of land in one year planted with several types of plants, both planted at the same time or slightly different times. The development of pests and diseases tends to occur more easily in monoculture cropping patterns because food sources for pests and pathogens are always available. On the other hand, a polyculture cropping pattern followed by a crop rotation pattern can break the life cycle of pests and diseases.Crop rotation has many advantages. In some organic crop cultivation systems, crop rotation is highly recommended. Some of the advantages of crop rotation are that it can reduce the intensity of pest or disease attacks, increase soil fertility, and crop rotation is highly recommended. Some of the advantages of crop rotation are that it reduces the intensity of pest or disease attacks, increases soil fertility, and is able to form a stable micro-ecosystem. In addition, in the agribusiness world, several types of commodities, especially vegetables, are able to meet the desired market demand.